2018
DOI: 10.1177/0017896918799799
|View full text |Cite
|
Sign up to set email alerts
|

Formative research to underpin a text messaging home safety intervention for young mothers

Abstract: Objective: Unintentional injury is the leading cause of death for infants and young children in the USA, and the children of young mothers are at an even higher risk. Mobile health (mHealth) interventions have been successful in promoting behaviour change for many health conditions. This study assessed interest in mSafety, a text and video messaging mHealth intervention targeting injury prevention knowledge, behaviour and self-efficacy in young mothers. Design: Interviews with young mothers were conducted usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 16 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…This finding concurs with a mock texting study conducted by Sharifi and colleagues who found that parents expressed a desire for specific, action-oriented advice, such as tips on healthy meals and local PA opportunities (Sharifi et al, 2013). Studies similar to ours have shown that including email and websites with the text messages enhances interactivity and provides access to more information (Mello et al, 2018; Sharifi et al, 2013), a practice called SMS Plus (Spohr et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…This finding concurs with a mock texting study conducted by Sharifi and colleagues who found that parents expressed a desire for specific, action-oriented advice, such as tips on healthy meals and local PA opportunities (Sharifi et al, 2013). Studies similar to ours have shown that including email and websites with the text messages enhances interactivity and provides access to more information (Mello et al, 2018; Sharifi et al, 2013), a practice called SMS Plus (Spohr et al, 2015).…”
Section: Discussionmentioning
confidence: 59%
“…There is a reported demand for education related to practical management methods among parents of infants and toddlers to reinforce the safety of their children at home [5]. The results of this study also showed that demonstrations and practice using safety equipment are effective educational strategies [7,29].…”
Section: Chnrmentioning
confidence: 84%
“…It is a key element in the success of teaching methods and improves learning outcomes [35,36]. According to a study by Mello et al [29] analyzed in this review, the results were positive after feedback was shared by a supervisor during interventions for the prevention of safety accidents aimed at young mothers. Faculty feedback is a teaching method that encourages complete learning, and previous studies have reported high satisfaction among trainees using this method; therefore, these findings support the results of this study [37].…”
Section: Chnrmentioning
confidence: 97%
See 2 more Smart Citations